THE EFFECT OF COMMUNICATION ON EMPLOYEE MORALE AT STIE TRISNA NEGARA EAST OKU - Garaika Garaika; Muhammad Junaidi; Yansahrita Yansahrita (STMIK Pringsewu, 2021)
Human resources are a very important thing in the organization. However, a process that takes place cannot be separated from human intervention. STIE Trisna Negara must reposition and recalculate the internal potential to then determine the steps that must be taken for the future of the region. A closer look at the conditions of work enthusiasm of STIE Trisna Negara employees, with various implications that arise and efforts to encourage morale that has been given with the symptoms that illustrate employee morale, is not under expectations. These conditions have an impact on the performance of STIE Trisna Negara employees not yet optimal under expectations. While the analysis tool used is simple linear regression analysis and using a t-test. The results of the qualitative analysis show that the communication variable (X1) indicator of knowledge gets a low score. Furthermore, the morale variable (Y) which becomes a weakness is discipline. The results of the quantitative analysis showed that partial communication (X1) had a significant effect on morale (Y) at STIE Trisna Negara East Oku. This conclusion is obtained partially, it is known that communication (X1) has a significant effect on morale (Y) at STIE Trisna Negara, East Oku. This is shown from the t-value of the communication variable (X1) = 9,657